Taxonomic revision of Trypanidius Blanchard, 1846 in South America (Insecta: Coleoptera: Cerambycidae) - Carelli, Allan; Monné, Marcela L.; Machado, Vanessa Souza (Zootaxa, 2013)
The genus Trypanidius Blanchard, 1846 includes 15 species in the Neotropical Region, nine of which occur in South America. In this contribution, the genus and South American species are redescribed and Trypanidius mimicavus sp. nov. is described from Bolivia. New distributional data are given for T. andicola Blanchard, 1846; T. dimidiatus Thomson, 1860; and T. notatus (Fabricius, 1787). All species are illustrated and a key to all species is provided.